The impact of business strategy on the relationship between voluntary disclosure of carbon emissions and firm value - Kim, Suyon (Edelweiss Applied Science and Technology, 2024)
This research examines the influence of firms' voluntary disclosure of carbon emissions on their value in the Korean capital market, with a particular focus on the role of business strategy. This study employs data from Korean companies that are involved in the Carbon Disclosure Project to investigate the impact of these disclosures on the value of the firm. The research classifies firms into prospector, analyzer, and defender stages according to their business strategies. The research findings suggest that the voluntary disclosure of carbon emissions has a negative impact on the overall value of a company. When examining the relationship with business strategy, firms in the prospector stage are seen as actively adopting environmental responsibility for long-term sustainability by voluntarily disclosing information, which may improve the value of the firm.